UPAYA PENCEGAHAN STUNTING MELALUI KEGIATAN SOSIALISASI DI DESA SERUNI MUMBUL, KECAMATAN PRINGGABAYA, KABUPATEN LOMBOK TIMUR - Faradila, Nurul; Zikri, Mahya; Anuggrah, Anggun; Lingga, Shelvya Aprya; Toyyibah, Zurriyatun; Ligasari, Via; Pebrianti, Baiq Tata Maharani; Ramdhani, Yusril Ibtida; Saputra, Andika; Zinuraen, Ahmad (Jurnal Wicara, 2025)
Stunting remains a chronic nutritional problem that significantly affects children's physical growth and cognitive development. East Lombok Regency, particularly Seruni Mumbul Village, is one of the regions with a relatively high prevalence of stunting, thus requiring prevention efforts through community education. The purpose of this activity was to improve community knowledge regarding stunting, its causes, long-term impacts, and preventive measures that can be applied at the household level. The activity was carried out through a socialization program at Posyandu Gumbang Sari involving pregnant women, mothers with toddlers, and posyandu cadres. The stages of the activity included delivering educational materials, interactive discussions, practical training on preparing balanced nutrition menus using local food sources, and evaluation through pre-test and post-test. The results indicated an increase in community understanding of the importance of balanced nutrition, proper parenting, and regular child growth monitoring. The community also showed high enthusiasm in participating and demonstrated the ability to apply the knowledge in daily practices. Thus, this socialization program successfully achieved its objectives, namely enhancing the awareness and understanding of Seruni Mumbul Village community in sustainable stunting prevention efforts.